2016
DOI: 10.1016/j.onehlt.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Is there a Lyme-like disease in Australia? Summary of the findings to date

Abstract: Lyme Borreliosis is a common tick-borne disease of the northern hemisphere caused by the spirochaetes of the Borrelia burgdorferi sensu lato (B. burgdorferi s. l.) complex. It results in multi-organ disease with arthritic, cardiac, neurological and dermatological manifestations. In the last twenty-five years there have been over 500 reports of an Australian Lyme-like syndrome in the scientific literature. However, the diagnoses of Lyme Borreliosis made in these cases have been primarily by clinical presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 138 publications
(251 reference statements)
1
50
0
Order By: Relevance
“…Currently in Australia, the ecology, epidemiology, and incidence of human tick-borne diseases remains largely a matter of conjecture, having received little scientific study compared with many other parts of the world (Graves and Stenos, 2017). Despite significant national interest, including a federal government senate inquiry (Radcliffe et al, 2016), the prevailing scientific opinion concludes that Lyme borreliosis (caused by B. burgdorferi sensu lato), for example, is absent from Australia (Chalada et al, 2016;Irwin et al, 2017). In the unique Australian environment, long isolated in geological terms, it is likely that unidentified tick-host life cycles have evolved that may contribute to zoonotic illness when humans encroach these sylvatic ecologies and become exposed to native ticks.…”
Section: Discussionmentioning
confidence: 99%
“…Currently in Australia, the ecology, epidemiology, and incidence of human tick-borne diseases remains largely a matter of conjecture, having received little scientific study compared with many other parts of the world (Graves and Stenos, 2017). Despite significant national interest, including a federal government senate inquiry (Radcliffe et al, 2016), the prevailing scientific opinion concludes that Lyme borreliosis (caused by B. burgdorferi sensu lato), for example, is absent from Australia (Chalada et al, 2016;Irwin et al, 2017). In the unique Australian environment, long isolated in geological terms, it is likely that unidentified tick-host life cycles have evolved that may contribute to zoonotic illness when humans encroach these sylvatic ecologies and become exposed to native ticks.…”
Section: Discussionmentioning
confidence: 99%
“…and Babesia spp. [21], and the geographical distribution of I. holocyclus appears to largely coincide with that of the LD-like cases reported in the scientific literature in Australia [12]. Although there are another 18 species of Ixodes tick species described in Australia [22], all are confined to the Australian continent; most of these have highly restricted host ranges and/or enzootic distributions, and rarely bite humans [22].…”
Section: Discussionmentioning
confidence: 79%
“…Previous meta-transcriptomic studies targeting arthropod viromes have revealed an abundance of novel and often highly divergent viruses (14, 23-25, 32). To date, however, there has been no study of the diversity of tick-associated viruses in Australia, nor of whether any of these viruses might play a role in tick-borne disease, despite the controversy surrounding tick-borne disease in this country (6, 7). Importantly, we also used the RNA-Seq meta-transcriptomic data generated here to search for the presence of known tick-associated pathogens, particularly the bacteria B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cases of tick-borne bacterial infection, particularly Lyme disease, are becoming increasingly frequent across parts of North America and Europe (4, 5). In Australia, Lyme disease is not recognized as endemic by the scientific nor medical communities, although controversy over its presence along the eastern coast of Australia has raged since the mid-1980s (6-8). Importantly, the species of ticks known to act as a vector of the disease are not found in Australia, and detailed studies involving microscopy, culturing, PCR, and metagenomic techniques indicate that the causative bacterial agent, Borrelia burgdorferi senso lato, is not present in Australian ticks (6, 7).…”
mentioning
confidence: 99%
See 1 more Smart Citation